Optimization of family planning service in Ukraine in the realization of modern strategy of woman health maintenance - Ю. Г. Антипкін; В. В. Камінський; Т. Ф. Татарчук (Publishing House TRILIST, 2017)
The primary objective of the reproductive health services system and its individual institutions are, namely: to implement the strategy of women management starting from their fetal life to the old age and ensure quality of life in adolescence, reproductive and postmenopausal periods. Maternal and child death rates are above respectives rates in European countries, and utilization rate of modern contraceptive methods in Ukraine remains low. This can be explained by both, poor awareness of women and insufficient training of medical personnel. In this context, the top priority still is awareness-raising and further implementation of the strategy on reliable contraception means and methods along with effective preconception care as a potent component of family planning. Taking into account modern global trends, the principal goal of Family Planning Service in Ukraine is to improve women's quality of life and time of active ageing, which achievement can be facilitated by the implementation of 3 priority tasks: • continued realization of the strategy on reliable contraception use and implementation of effective preconception care to abortions prevention and maternal and newborns mortality rates reduction; • reduction cardiovascular and oncological diseases incidence rate in women through development and implementation of respective screening programs, informational and preventive measures; • implementation of best international practices with respect to Family Planning Service efficacy, review and update of family planning clinical protocol with further implementation of such practices at the national and regional levels. Considering this, the Resolution of Advisory Board outlines the main tasks for the implementation of modern international experience and its further implementation at the national level, and amendments to clinical protocol of primary, secondary (specialized) and tertiary (highly specialized) medical care (approved by the order of MOH of Ukraine No. 59 dated January 21, 2014) "Family Planning". The main additions and comments touched upon the issues of micronutrient status and reproductive health of women, contraceptive methods for women in perimenopause, counseling and selection of contraceptive methods for HIV-positive women. Particular attention was paid to counseling and selection of contraceptive methods for women military personnel.